Issues of Polylingual Education in the Republic of Tatarstan (Gumilyov Journal of Pedagogy, 2025)
Polylingual education is a purposeful process aimed at fostering students’ engagement with multilingualism and their appreciation of multicultural societies and the global community. The primary means of achieving this is the mastery of more than two languages, each serving as a tool for acquiring specialized knowledge and facilitating intercultural communication. This article presents the experience of the Republic of Tatarstan in organizing polylingual education, focusing on the organizational and pedagogical conditions of the polylingual approach to academic preparation, communicative competence, and intercultural interaction among students, as well as the factors ensuring the successful implementation of polylingual education in the region. The study’s objective is to monitor polylingual education and evaluate its effectiveness in schools across the Republic of Tatarstan. The research findings, drawn from studies conducted in the republic’s schools, confirm the significance of the polylingual approach in contemporary education. A classification of educational institutions implementing polylingual education was developed as part of the study. Particular attention is given to the experience of the State Autonomous Educational Institution “Polylingual Complex ‘Adymnar’ – Path to Knowledge and Harmony” in Tatarstan, which is focused on creating a modern and effective polylingual educational environment. The scientific and practical significance of the article lies in its analysis of regulatory documents and legislative acts governing the educational system of the Republic of Tatarstan, a qualitative content analysis of reports on polylingual education practices, surveys and questionnaires of teachers and school administrators to gauge their attitudes toward polylingual education and identify barriers to its effective implementation, expert interviews with stakeholders to obtain professional assessments and suggestions for improvement, and an empirical analysis of academic performance and the development of communicative skills among students in polylingual classes.  The study demonstrates that polylingual education enhances students’ academic, cognitive, and aesthetic development, fosters communicative abilities, and cultivates a value-based appreciation of the cultural characteristics of diverse peoples.